MtDNA diversity among four Portuguese autochthonous dog breeds: a fine-scale characterisation - Santa-Rita Pedro; Pereira Filipe; Pereira Luísa; van Asch Barbara; Lima Manuela; Amorim António (BMC Genetics, 2005)
Abstract Background The picture of dog mtDNA diversity, as obtained from geographically wide samplings but from a small number of individuals per region or breed, has revealed weak geographic correlation and high degree of haplotype sharing between very distant breeds. We aimed at a more detailed picture through extensive sampling (n = 143) of four Portuguese autochthonous breeds – Castro Laboreiro Dog, Serra da Estrela Mountain Dog, Portuguese Sheepdog and Azores Cattle Dog-and comparatively reanalysing published worldwide data. Results Fifteen haplotypes belonging to four major haplogroups were found in these breeds, of which five are newly reported. The Castro Laboreiro Dog presented a 95% frequency of a new A haplotype, while all other breeds contained a diverse pool of existing lineages. The Serra da Estrela Mountain Dog, the most heterogeneous of the four Portuguese breeds, shared haplotypes with the other mainland breeds, while Azores Cattle Dog shared no haplotypes with the other Portuguese breeds. A review of mtDNA haplotypes in dogs across the world revealed that: (a) breeds tend to display haplotypes belonging to different haplogroups; (b) haplogroup A is present in all breeds, and even uncommon haplogroups are highly dispersed among breeds and continental areas; (c) haplotype sharing between breeds of the same region is lower than between breeds of different regions and (d) genetic distances between breeds do not correlate with geography. Conclusion MtDNA haplotype sharing occurred between Serra da Estrela Mountain dogs (with putative origin in the centre of Portugal) and two breeds in the north and south of the country-with the Castro Laboreiro Dog (which behaves, at the mtDNA level, as a sub-sample of the Serra da Estrela Mountain Dog) and the southern Portuguese Sheepdog. In contrast, the Azores Cattle Dog did not share any haplotypes with the other Portuguese breeds, but with dogs sampled in Northern Europe. This suggested that the Azores Cattle Dog descended maternally from Northern European dogs rather than Portuguese mainland dogs. A review of published mtDNA haplotypes identified thirteen non-Portuguese breeds with sufficient data for comparison. Comparisons between these thirteen breeds, and the four Portuguese breeds, demonstrated widespread haplotype sharing, with the greatest diversity among Asian dogs, in accordance with the central role of Asia in canine domestication.